Redescription of Anovia circumclusa (Gorham) (Coleoptera: Coccinellidae: Noviini), with first description of the egg, larva, and pupa, and notes on adult intraspecific elytral pattern variation - Forrester, Juanita A.; Vandenberg, Natalia J.; Mchugh, Joseph V. (Zootaxa, 2009)
Anovia circumclusa (Gorham), a neotropical lady beetle, recently was recorded in North America for the first time. Previously, only the adult form of this beneficial predator had been described. This paper provides a redescription of the adult and the first descriptions of the egg, larva, and pupa. Diagnostic characters for the genus and species are given, and intraspecific color variation in Anovia adults is discussed.